Quantum mechanics : a modern and concise introductory course - Bes, Daniel R.
Abelian symmetry -- Abelian transformation -- Actión -- Adjoint vector -- Ag atom -- Alkali atoms -- Allowed transitións -- Alpha particle -- Angular momentum -- Additión -- Commutatión relatión -- Matrix treatment -- Orbital -- Angular subspace -- Anthropocentric foundatión of quantum...